SEASONAL VARIATION IN SELECTED HEAVY METAL CONCENTRATIONS IN THE NANDALAR ESTUARY EAST COAST OF TAMIL NADU-INDIA - ANUSIYA, R.; SUKUMARAN, M. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2022)
Estuaries are dynamic environments with respect to metal speciation, as many of the physicochemical parameters that affect metal equilibria are subject to change as fresh and marine waters mix. pH, hardness, dissolved organic matter concentration, and ionic strength will all significantly affect the partitioning of copper within and between solid and solution phases. Heavy metals have been present in nature for many years, but their toxicity is increasing as a result of anthropogenic activities. There is an increase in heavy metal contamination in many inland waters as well as estuarine ecosystems nowadays. The aim of the present study is to evaluate seasonal variation in some selected heavy metal concentrations in the Nandalar estuary on the east coast of Tamil Nadu, India, during the 2020 to 2021 period. The monsoon season saw the highest appearance of followed the order of Cu (0.043mg/L) > Cr (0.027mg/L) > Zn (0.024mg/L) > Pb (0.023mg/L) > Ni (0.012mg/L) > Cd (0.007mg/L) > Hg (>0.00001mg/L) metals compared with the pre and post monsoon seasons, while present metals were higher than the Fisheries and aquatic life standard reference value. Overall, the metal of Cu (0.032 to 0.043 mg/L) was the higher concentration found to be in the Nandalar estuary. The seasonal variation analysis showed to higher content of copper was observed in Nandalar estuary, Tamil Nadu.